MEMINIMALISIR TINGKAT KESULITAN SISWA DALAM BELAJAR MATA PELAJARAN ILMU PENGETAHUAN ALAM PADA SISWA SMP/MTS - Noor Fanika (Bioilmi: Jurnal Pendidikan, 2021)
Students have different levels of difficulty in understanding Natural Science material. This study aims to determine the independence of students in minimizing learning difficulties experienced by students themselves. The research method using quantitative descriptive type was carried out by survey method via google form online. The technique of collecting data through a questionnaire instrument. From filling in the google form, respondents collected 13 students at the SMP / MTs level from various schools and different regions (Kudus and Jepara). This research was conducted in the even semester of 2020/2021. The results showed that learning media that were attractive in learning science, increased student learning independence and increased student interest in learning could minimize the difficulty of learning science concepts. Another result shows that students who have high interest in learning are still low. Learning independence that is not optimal and student interest in learning is still low causing difficulties in learning Natural Sciences. Learning independence is a predictor of learning outcomes.